The Influence of Education, Database and Technological Innovation on the Implementation of the Internet of Things - Isnawati, Isnawati; Ali, Hapzi (Siber International Journal of Education Technology (SIJET), 2024)
Analysis of the Determinants of the Influence of Education, Databases, and Technological Innovation on the Implementation of the Internet of Things is an analysis of published works in the subject of ESSB. In order to provide a basis for future research, this article aims to generate hypotheses about the correlation between variables. Academic databases such as Google Scholar, Mendeley, and others are part of the research object. This research utilizes a literature review strategy based on the use of publicly accessible electronic resources, such as e-books and journals. Descriptive qualitative analysis was used. The following are the findings of this analysis: 1) Education in the Implementation of the Internet of Things; 2) Database in Internet of Things Implementation Determination Analysis; 3) Technology Innovation in Internet of Things Implementation Determination Analysis.